The Evaluation of Brass and Low Carbon Steel Corrosion in Gabraun Water - Abdussalam Abdallah Mohammed Gebril , Ali Elzarog Ali (Journal of Pure & Applied Sciences, 2020)
This work aimed to study the effect of Gabraun`s water on corrosion of brass and low carbon steel. The corrosion tests were carried out at room temperature. The test solution used was Gabraun water samples. From the results obtained, the weights of all the specimens after the immersion in Gabraun`s water were decreased. After the end of the experiments, the color of the Gabraun water samples that was used for the brass specimens was changed to dark blue color, but for the low carbon steel the color of the water did not change. During the corrosion tests period, the Gabraun water in the beakers was decreased about 50mL/week, this lack was substituted continuously by Gabraun water during the tests period. This addition of water, increased the concentration of the salts of the Gabraun water samples. This increment was played a role in the corrosion process. The average corrosion rate for the low carbon steel is less than yellow copper specimens. The Langelier Saturation Index (LSI) showed that the Gabraun water sample was not corrosive medium, also it showed all the Gabroun waters samples after testing all the specimens were not corrosive medium. The Pourbaix diagrams for both copper and iron in the water at 25oC showed both copper and iron are not corrode metals.